Data science in R a case studies approach to computational reasoning and problem solving - Nolan, Deborah Ann; Lang, Duncan Temple (Chapman & Hall/CRC the R series, 2015)
Data Science in R: A Case Studies Approach to Computational Reasoning and Problem Solving illustrates the details involved in solving real computational problems encountered in data analysis. It reveals the dynamic and iterative process by which data analysts approach a problem and reason about different ways of implementing solutions